Gastrina: hormona de múltiples funciones - Marambio G., Andrés; Watkins S., Guillermo; Jans B., Jaime (Revista Hospital Clínico Universidad de Chile, 2012)
Gastrin is a polypeptide hormone secreted primarily by G cells of the gastric antrum. Its main function is the regulation of gastric acidity, through the release of histamine, which ultimately acts on the parietal cell. There are a number of pathological conditions characterized by persistent hypergastrinemia will cause various effects, from peptic disease to cancer. Most research points to clarify their involvement in processes of proliferation of different cell types and thus to find a treatment for cancer. Intermediates molecules have been described for the metabolism of gastrin, which also possess the property of stimulating the proliferation of various cell lines and participated in processes of cell migration and invasion. Using molecular bioengineering has been able to modify the original molecule to create receptor antagonist and thus able to address some of the associated diseases. Much of this hormone, described over a century ago, is still unknown